2022
DOI: 10.3390/ph15030378
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Wnt/Beta-Catenin Signaling in HPV-Positive Head and Neck Squamous Cell Carcinoma

Abstract: Wnt/Beta-Catenin signaling is involved in the carcinogenesis of different solid malignant tumors. The interaction of Creb-binding protein (CBP) with Beta-Catenin is a pivotal component of the Wnt/Beta-Catenin signaling pathway. The first aim of this study was to evaluate the association of CBP expression with survival in patients with human papillomavirus (HPV)-positive head and neck squamous cell carcinoma (HNSCC). Second, the in vitro effects of the inhibition of CBP/Beta-Catenin interaction were analyzed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Synergistic effects were observable at 2 Gy which is also favorable from a clinical standpoint, since sessions with doses of 2 Gy are used in the primary care of HNSCC tumors [ 30 ]. These results are in line with other studies, that showed increased cytotoxicity of irradiation in combination with a targeted drug in HNSCC cells [ 24 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Synergistic effects were observable at 2 Gy which is also favorable from a clinical standpoint, since sessions with doses of 2 Gy are used in the primary care of HNSCC tumors [ 30 ]. These results are in line with other studies, that showed increased cytotoxicity of irradiation in combination with a targeted drug in HNSCC cells [ 24 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…As noted, no viable results could be obtained for the SCC154 cells, since these cells need cell–cell contact to proliferate. Similarly, in lung adenocarcinoma, breast cancer, colorectal cancer, and HNSCC a reduced migratory potential upon Wnt pathway inhibition has been observed in the past [ 24 , 25 , 32 34 ]. In addition, probing for cleaved Caspase 3/7 upon MSAB revealed induction of apoptosis in treated HNSCC cells.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This repression of Siah-1 by E6 and E7 indicates their direct role in the nuclear accumulation of β-CATENIN in HPV-associated OPSCC. Interestingly, blockade of the WBC pathway by a specific inhibitor of Creb-binding protein (CBP) has been demonstrated to be specifically effective in the HPV-positive HNSCC cell line SCC154 compared to the HPV-negative HNSCC cell line Cal27 (Brkic et al 2022). Moreover, MSAB, a small inhibitor of β-CATENIN, has been proven to have antineoplastic effects in HNSCC as well-supporting the oncogenic role of the WBC pathway in HNSCC (Maier et al 2023).…”
Section: Introductionmentioning
confidence: 99%